2021
DOI: 10.3917/rimhe.044.0053a
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable mobility schemes in companies: a thwarted legitimacy?

Abstract: Les dispositifs de mobilité durable en entreprise proposent aux salariés l’usage de moyens de mobilité décarbonés pour effectuer leurs déplacements pendulaires et professionnels. Objets encore peu étudiés en sciences de gestion, ces dispositifs, issus d’une double pression normative et sociétale, apparaissent éloignés des préoccupations de performance économique et considérés comme périphériques ou subsidiaires. La question de leur légitimité perçue en interne est donc posée ainsi que celle de l’identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Initial studies in management science found that initiatives promoting sustainable corporate mobility as part of a broader CSR strategy are often considered peripheral and lack legitimacy. This, in turn, impedes their adoption and implementation (Volz-Tollet, 2021). However, as demonstrated previously, a more sustainable way of thinking about the mobility of employees is pressing.…”
Section: Sustainable Mobility As Part Of a Csr Strategymentioning
confidence: 96%
“…Initial studies in management science found that initiatives promoting sustainable corporate mobility as part of a broader CSR strategy are often considered peripheral and lack legitimacy. This, in turn, impedes their adoption and implementation (Volz-Tollet, 2021). However, as demonstrated previously, a more sustainable way of thinking about the mobility of employees is pressing.…”
Section: Sustainable Mobility As Part Of a Csr Strategymentioning
confidence: 96%